The Virtualization of Engineering Careers at UNET as an Alternative for Academic Prosecution (LACCEI, 2024)
This research consisted on the systematization of a virtualization experience of the Engineering Careers of the National Experimental University of Táchira (UNET), with the purpose of maintaining the academic continuity of students, interrupted by the health emergency of COVID-19. The study methodology has a descriptive scope and is systematized according to the phases of the ADDIE model (analysis, design, development, implementation, evaluation), articulated in a complex and recursive process between the different actors involved in the virtualization process.